Advanced approach Using Neural Network for Intelligent Automated Production System - Anas Mohammad Quteishat (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of cutting-edge tooling and processes is regarded as an important component in bridging the gap between design and output. The most significant advantage of a fully automated computer-aided planning approach has been Intelligent Automated Planning System (IPS) To investigate how artificial neural networks can be used to assist IAPS in solving problems. A collection of strategies suitable for all applications is defined here, as well as how far they are from a potential implementation of a universal IAPS algorithm. Intelligent development with advanced LSTM neural network algorithms and automation